Acceptance of a mobile telepresence robot used to teach adapted physical activity to isolated older adults: extending and testing the technology acceptance model - Elodie Navarro; Jean-Jacques Temprado; Nicolas Mascret (Frontiers Media S.A., 2024)
This study aimed to investigate the acceptance of adapted physical activity (APA) by teachers and students before the use of a mobile telepresence robot (MTR), used to remotely supervise isolated older adults' physical activity. While previous studies have shown MTR to be fairly well accepted by older adults, nothing is known about its acceptance by APA teachers themselves. However, if they did not accept it, the MTR would not be used in the end. This would be a public health issue because isolated older adults would not benefit from supervised APA, yet beneficial to their health. To this end, 334 participants answered a survey that measured different psychological variables, based on the technology acceptance model (TAM). Student's t-tests and structural equation modeling were used for data processing. Results showed that, before use, there was not any significant difference between teachers' and students' acceptance of the MTR. Then, perceived usefulness for teaching APA, perceived ease of use, perceived enjoyment, and intention to use the MTR were lower than the mean of the scale, while perceived usefulness for older adults was higher than the mean of the scale. Finally, this study has validated an extended version of the TAM (including the need for competence and MTR self-efficacy), which allowed it to explain 84.3% of the variance of the students' and APA teachers' intention to use the MTR for teaching APA to isolated older adults. Initial obstacles to the use of the MTR seem to exist on the part of APA teachers, prior to their first use, whereas this is not the case for older adults. APA teachers' acceptance should therefore be investigated in future studies to examine whether this trend is confirmed after the effective use of the MTR.